A Hyper-Attenuated Variant of Rift Valley Fever Virus Generated by a Mutagenic Drug (Favipiravir) Unveils Potential Virulence Markers - Borrego, Belén; Brun, Alejandro (Frontiers in Microbiology, 2021)
In a previous work, we showed that favipiravir, a promising drug with antiviral activity against a number of RNA viruses, led to the extinction of RVFV from infected cell cultures. Nevertheless, certain drug concentrations allowed the recovery of a virus variant showing increased resistance to favipiravir. In this work, we characterized this novel resistant variant both at genomic and phenotypic level in vitro and in vivo. Interestingly, the resistant virus displayed reduced growth rates in insect cells and was highly attenuated but still immunogenic in vivo. Some amino acid substitutions were identified in the viral RNA-dependent RNA-polymerase (RdRp) gene and in the encoded IFN antagonist NSs gene, in catalytic core motifs and nuclear localization associated positions respectively. These data may help to characterize novel potential virulence markers, offering additional strategies for further safety improvements of RVF live attenuated vaccine candidates.